Robust Adaptive Control of a Hydraulic Press. Issue 2 (2020) - Macchelli, A.; Barchi, D.; Marconi, L.; Bosi, G.
Abstract: The aim of this paper is to illustrate the design and the simulative validation of an adaptive controller developed for an hydraulic press. With respect to controllers actually implemented, the proposed solution assures similar performances in nominal conditions, but it is simpler to be tuned and it is able to estimate the leakage inside the hydraulic piston. Such an estimate is used to maintain the performances acceptable in a wide set of operative conditions and for predictive maintenance. By using singular perturbation arguments, we show robustness to slowly increasing leakage gains, which is a typical situation in a real-world application. The control scheme is validated on a simulative Simscape model.